Prevalence and Clinical Characteristics of SARS-CoV-2 Confirmed and Negative Kawasaki Disease Patients During the Pandemic in Spain - Fernández-Cooke, Elisa; Grasa, Carlos D.; Domínguez-Rodríguez, Sara; Barrios Tascón, Ana; Sánchez-Manubens, Judith; Anton, Jordi; Mercader, Beatriz; Villalobos, Enrique; Camacho, Marisol; Navarro Gómez, María Luisa; Oltra Benavent, Manuel; Giralt, Gemma; et al. (Frontiers in Pediatrics, 2021)
Introduction: COVID-19 has a less severe course in children. In April 2020, some children presented with signs of multisystem inflammation with clinical signs overlapping with Kawasaki disease (KD), most of them requiring admission to the pediatric intensive care unit (PICU). This study aimed to describe the prevalence and clinical characteristics of KD SARS-CoV-2 confirmed and negative patients during the pandemic in Spain. Material and Methods: Medical data of KD patients from January 1, 2018 until May 30, 2020 was collected from the KAWA-RACE study group. We compared the KD cases diagnosed during the COVID-19 period (March 1–May 30, 2020) that were either SARS-CoV-2 confirmed (CoV+) or negative (CoV–) to those from the same period during 2018 and 2019 (PreCoV). Results: One hundred and twenty-four cases were collected. There was a significant increase in cases and PICU admissions in 2020 (P-trend = 0.001 and 0.0004, respectively). CoV+ patients were significantly older (7.5 vs. 2.5 yr) and mainly non-Caucasian (64 vs. 29%), had incomplete KD presentation (73 vs. 32%), lower leucocyte (9.5 vs. 15.5 × 109) and platelet count (174 vs. 423 × 109/L), higher inflammatory markers (C-Reactive Protein 18.5vs. 10.9 mg/dl) and terminal segment of the natriuretic atrial peptide (4,766 vs. 505 pg/ml), less aneurysm development (3.8 vs. 11.1%), and more myocardial dysfunction (30.8 vs. 1.6%) than PreCoV patients. Respiratory symptoms were not increased during the COVID-19 period. Conclusion: The KD CoV+ patients mostly meet pediatric inflammatory multisystem syndrome temporally associated with COVID-19/multisystem inflammatory syndrome in children criteria. Whether this is a novel entity or the same disease on different ends of the spectrum is yet to be clarified.